THE SALIVARY GLAND CHROMOSOMES OF CULEX PIPIENS MOLESTUS - J.D. Amirkhanian (Tehran University of Medical Sciences, 1974)
The polygene chromosomal pattern together with the somatic and meiotic chromosomes of the autogenous Tehran strain of Culex pipiens molestus is described. The first and third chromosomes are metacentric, the second one is slightly submetacentric. Each chromosome has well-defined, large puffed characteristic centromeres. Randomly distributed asynaptic regions on the polytens chromosomes are indicative of gene differences, on homologous arms which occasionally involve the centromeres. Puffs are sometimes noticeable on the chromosomal arms. A permanent puff is located on the first and third chromosome. The morphology of the first meiotic metaphase chromosomes is characteristic of the species. The existence of interchromosomal and intrachromosomal connective, and also stickiness of the ends of the salivary chromosomes to one another, is the major difficulty in the preparation of the salivary gland chromosomes of Culex, which has been overcome by the technique for the mosquito chromosome spreads.